(untitled) (Bioagro, 2026)
Pachycereus weberi is a columnar cactus endemic from Mexico. Despite the great diversity of research on fruits of other cacti, there is no information on the nutraceutical and nutritional attributes of this wild species. Therefore, in the present investigation physical, mineral, nutritional and antioxidant components om fruits from wild populations of three localities of the Mixteca Poblana. The average weight of the fruits was 84.21 g, with 43.86 % pulp and 56.14 % epicarp with spines. Considerable average concentrations of phosphorus, calcium, magnesium, sulfur and zinc were found, as well as lipids, proteins and carbohydrates. The average concentration of phenolic compounds was 263.80 mg GAE 100 g-1 fresh weight (f.w.); 6.19 mg QE 100 g-1 f.w. of flavonoids; 23.93 mg AAE g-1 f.w. of vitamin C; and, 19.41 mg g-1 f.w. of total betalains in the pulp. Finally, the average antioxidant activity by the ABTS and FRAP methods was 3.68 and 8.81 mM TE 100 g-1 f.w., respectively. The results of this research will contribute with information to revalue the conservation of this species, which could promote its management in sustainable agricultural practices and highlight the importance of local biodiversity, as well as its nutritional contribution and the benefit to the health of consumers.